Sensitivity towards HDAC inhibition is associated with RTK/MAPK pathway activation in gastric cancer. Issue 10 (22nd August 2022) - Seidlitz, Therese; Schmäche, Tim; Garcίa, Fernando; Lee, Joon Ho; Qin, Nan; Kochall, Susan; Fohgrub, Juliane; Pauck, David; Rothe, Alexander; Koo, Bon‐Kyoung; Weitz, Jürgen; Remke, Marc; et al.
Abstract: Gastric cancer ranks the fifth most common and third leading cause of cancer‐related deaths worldwide. Alterations in the RTK/MAPK, WNT, cell adhesion, TP53, TGFβ, NOTCH, and NFκB signaling pathways could be identified as main oncogenic drivers. A combination of altered pathways can be associated with molecular subtypes of gastric cancer. In order to generate model systems to study the impact of different pathway alterations in a defined genetic background, we generated three murine organoid models: a RAS‐activated ( Kras G12D, Tp53 R172H ), a WNT‐activated ( Apc fl/fl, Tp53 R172H ), and a diffuse ( Cdh1 fl/fl, Apc fl/fl ) model. These organoid models were morphologically and phenotypically diverse, differed in proteome expression signatures and possessed individual drug sensitivities. A differential vulnerability to RTK/MAPK pathway interference based on the different mitogenic drivers and according to the level of dependence on the pathway could be uncovered. Furthermore, an association between RTK/MAPK pathway activity and susceptibility to HDAC inhibition was observed. This finding was further validated in patient‐derived organoids from gastric adenocarcinoma, thus identifying a novel treatment approach for RTK/MAPK pathway altered gastric cancer patients. Synopsis: The analysis of murine and human gastric tumor organoids uncovered an association between RTK/MAPK pathway activity and susceptibility to HDAC inhibition, thereby identifying a potential new treatment approach for gastric cancer patients. Three murine tumor organoid models with a defined genetic background were generated by altering frequently mutated pathways in gastric cancer. The organoid models were characterized concerning their phenotype, proteome expression pattern, and therapeutic response via a drug screen. RAS activation in murine tumor organoids led to a significantly increased sensitivity to HDAC inhibition. HDAC sensitivity was confirmed in patient derived gastric cancer organoids with MAPK pathway alterations. Abstract : The analysis of murine and human gastric tumor organoids uncovered an association between RTK/MAPK pathway activity and susceptibility to HDAC inhibition, thereby identifying a potential new treatment approach for gastric cancer patients.